Ozone therapy in the treatment of recurrent herpes labialis: a clinical case report (Research, Society and Development, 2020)
Herpes is one of the infectious diseases that grows the most worldwide, with 500,000 new cases every year. It is presented as a painful vesicular eruption, forming crusts that cause esthetic deformation and psychosocial distress. It is usually a self-limiting and recurrent disease with no cure available. This study aims to report an case in the literature of unusual treatment of a recurrent herpes simplex labialis with ozone therapy. A search for scientific articles was performed in the Pubmed, SciELO, and Embase databases for scientific basis and construction of the clinical case report. Female patient, 20 years old, with history of multiple recurrences of herpes labialis lesions, attended the clinical service with small perilabial vesicles after signs of itching and burning. Considering the previous history and lesion characteristics, a treatment was established for herpes labialis with ozone injection around the lesion associated with the topical use of ozonized sunflower oil. The clinical aspect of the lesion and related symptoms improved in a shorter period than the previous episodes. Ozone therapy was effective in this case of recurrent herpes labialis and further studies are required to create a clinical treatment protocol.